UPAYA PENINGKATAN PRODUKSI TANAMAN TOMAT (Solanum lycopersicum M.) DENGAN APLIKASI PUPUK DAUN DAN PUPUK KCL - Choirul Anam; Dian Eka Kusumawati; Yuyun Ayunda Apriliya (AGRORADIX : Jurnal Ilmu Pertanian, 2023)
Fertilization is a critical element in agricultural practices because plants need adequate and balanced nutrition to grow and develop well. Common obstacles faced in growing tomato plants, such as lack of nutrition or low yields. The aim of this research was to determine the effect of foliar fertilizer and KCl fertilizer doses on increasing the growth and production of tomato plants. The research was conducted from February to April 2022 in Jugo Village, Sekaran District, Lamongan Regency. This research used a factorial Randomized Block Design (RAK) procedure with two treatment factors. The first factor is the type of foliar fertilizer, consisting of 3 levels, including Growmore, Mamigro, and Gandasil D foliar fertilizer. The second factor, namely the dose of KCl fertilizer, consists of 3 levels, including no fertilizer (control), 100 kg/ha, and 150 kg/ha. Ha. The conclusion in this research is that there is an interaction between the type of foliar fertilizer treatment and the dose of KCl fertilizer on the parameters of plant height, number of leaves and number of branches at age. Treatments for various types of foliar fertilizer differ significantly in the parameters of number of fruit per plant, fruit diameter per plant, fruit weight per plant, and fruit weight per hectare. Mamigro leaf fertilizer treatment and a 150 kg dose of KCl fertilizer was the best treatment combination.